Prevalence of Leptospira spp. and Seoul hantavirus in brown rats (Rattus norvegicus) in four regions in the Netherlands, 2011-2015. Issue 1 (1st January 2018) - Maas, Miriam; De Vries, Ankje; Reusken, Chantal; Buijs, Jan; Goris, Marga; Hartskeerl, Rudy; Ahmed, Ahmed; Van Tulden, Peter; Swart, Arno; Pijnacker, Roan; Koene, Miriam; Lundkvist, Åke; et al.
ABSTRACT: Background: Brown rats ( Rattus norvegicus ) may carry pathogens that can be a risk for public health. Brown rats in the Netherlands were tested for the zoonotic pathogens Leptospira spp. and Seoul hantavirus (SEOV), in order to obtain insight in their prevalence. Methods and results: Cross-sectional studies were performed at four locations from 2011 to 2015. The rats were tested for Leptospira spp. using real-time PCR and/or culture resulting in a prevalence ranging between 33–57%. Testing for SEOV was done through an adapted human Seoul hantavirus ELISA and real-time RT-PCR. Although at several locations the ELISA indicated presence of SEOV antibodies, none could be confirmed by focus reduction neutralization testing. Conclusion: The results indicate a widespread presence of Leptospira spp. in brown rats in the Netherlands, including areas with a low leptospirosis incidence in humans. No evidence for circulation of SEOV was found in this study.